The Perceptions of Mathematics Teacher about Students’ Difficulties in Online Learning - Isnawati, Ayus Riana; Ardani, Riska Ayu (UIN Walisongo Semarang, 2023)
The Covid-19 explosion has changed all activities, including the learning process. The existence this pandemic makes all sectors try to find the best solution. This needs to be done so that all systems are well maintained. One solution during the pandemic is learning activities with online activities. Online learning without face to face certainly raises some problems. New activities make teachers and students must adapt to new learning conditions. In addition, various obstacles provide a paradigm that applying online learning is difficult. The difficulty of carrying out online learning is certainly not only felt by student but also teacher feel the same way. However, it is the teacher’s responsibility to address their difficulties and students’ difficulties. To determine an effective solution in overcoming students’ difficulties, further research is needed to determine the aspect that promote students’ difficulties in online learning. Through this survey research, researchers wanted to see how mathematics teacher’s perception about students’ difficulties when participating in online learning. Most teachers’ perceptions indicate that aspects of facilities and infrastructure, learning activities and environment are the main factors which promote students’ difficulties in online learning.Keywords: perception of athematics teacher, students’ difficulties, online learning